Effect of an educational intervention on the clinical competence for primary healthcare of rheumatic diseases in Mexican physicians (2016)
Objetive To measure the effect of an educational intervention on clinical competences for diagnosis and treatment of rheumatic diseases in primary healthcare physicians working in the Guadalajara Metropolitan Area, Jalisco, Mexico.Methodology Quasi-experimental study conducted in physicians from two primary health care units. The study was carried out in a 40 physicians sample, 21 in Group “A” (intervention) and 19 in Group “B” (control). The clinical competence for diagnosis and treatment of rheumatic diseases was measured in both groups by means of an instrument previously designed and validated (Kuder-Richardson reliability index =0,94).Results Clinical competence average score prior to intervention was 47 for Group “A” and 42 for Group “B”, while after the intervention it was 72 and 47 respectively, which shows statistically significant differences (Wilcoxon test, p0,05).Conclusions Clinical competence for diagnosis and treatment of rheumatic diseases in primary healthcare physicians is low; however, it can be improved by implementing educational interventions based on a constructivist approach.